Proctored Step by Step Training Program for GreenLight Laser Anatomic Photovaporization of the Prostate: A Single Surgeon's Experience - Sessa, Francesco; Campi, Riccardo; Granieri, Stefano; Tuccio, Agostino; Polverino, Paolo; Spatafora, Pietro; Sebastianelli, Arcangelo; Cocci, Andrea; Rivetti, Anna; Gacci, Mauro; Carini, Marco; Serni, Sergio; et al. (Frontiers in Surgery, 2021)
Objectives: To evaluate the feasibility and safety of a proctored step-by-step training program for GreenLight laser anatomic photovaporization (aPVP) of the prostate. Methods: Data from patients undergoing aPVP between January 2019 and December 2020 operated by a single surgeon following a dedicated step-by-step proctored program were prospectively collected. The procedure was divided into five modular steps of increasing complexity. Preoperative patients’ data as well as total operative time, energy delivered on the prostate and postoperative data, were recorded. Then, we assessed how the overall amount of energy delivered and the operative times varied during the training program. Surgical steps were analyzed by cumulative summation. Univariable and multivariable regression models were built to assess the predictors of the amount of energy delivered on the prostate. Results: Sixty consecutive patients were included in the analysis. Median prostate volume was 56,5 mL. The training program was succesfully completed with no intraoperative or meaningful post-operative complications. The energy delivered reached the plateau after the 40th case. At multivariable analysis, increasing surgeon experience was associated with lower amounts of energy delivered as well as lower operative times. Conclusions: A step-by-step aPVP training program can be safely performed by surgeons with prior endoscopic experience if mentored by a skilled proctor. Considering the energy delivered as an efficacy surrogate metrics (given its potential impact on persistent postoperative LUTS), 40 cases are needed to reach a plateau for aPVP proficiency. Further studies are needed to assess the safety of our step-by-step training modular program in other clinical contexts.